Efektivitas Perencanaan Pembelajaran IPA dengan Strategi Discovery Learning terhadap Hasil Belajar Kognitif Siswa Kelas 5 SDIT Annajiyah Tuban - Muhammad Abdullah Aslam Madani; Nurhaningtyas Agustin (Advances In Education Journal, 2026)
This research is motivated by the lack of variety in learning, especially in science learning. The science learning process tends to use conventional methods or models, and the science learning process does not pay attention to the level of students' understanding (cognitive) of the information conveyed. The purpose of this study is to describe the process of implementing science learning with the Discovery Learning strategy. This study uses a qualitative research method with a literature review research type. The research subjects were 1 Science subject teacher and 17 5th grade students at SDIT Annajiyah Tuban, consisting of 8 male students and 9 female students. Data collection techniques include observation and interviews. The results of the study indicate that the application of the Discovery Learning strategy in science learning is able to improve students' cognitive learning outcomes and is able to create meaningful learning and improve students' understanding, application, and analysis abilities in science learning.